2015
DOI: 10.1007/s12039-015-0937-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of polydispersity index as control parameter to study melting/freezing of Lennard-Jones system: Comparison among predictions of bifurcation theory with Lindemann criterion, inherent structure analysis and Hansen-Verlet rule

Abstract: Using polydispersity index as an additional order parameter we investigate freezing/melting transition of Lennard-Jones polydisperse systems (with Gaussian polydispersity in size), especially to gain insight into the origin of the terminal polydispersity. The average inherent structure (IS) energy and root mean square displacement (RMSD) of the solid before melting both exhibit quite similar polydispersity dependence including a discontinuity at solid-liquid transition point. Lindemann ratio, obtained from RMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 58 publications
(93 reference statements)
1
7
0
Order By: Relevance
“…The result has been shown to be consistent with one another, both qualitatively and quantitatively, in predicting the existence of terminal 3 polydispersity, beyond which freezing is not possible [9]. The Lindemann ratio, obtained from RMSD, has been shown to be intensely dependent on temperature [8].…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…The result has been shown to be consistent with one another, both qualitatively and quantitatively, in predicting the existence of terminal 3 polydispersity, beyond which freezing is not possible [9]. The Lindemann ratio, obtained from RMSD, has been shown to be intensely dependent on temperature [8].…”
Section: Introductionsupporting
confidence: 73%
“…In a recent study [8], in order to investigate the effect of polydispersity on the solid-liquid transition of the Lennard-Jones system [9], we have analyzed the model system using numerical simulations in three distinct ways, namely, by applying the empirical Lindemann criterion of melting, the inherent structure analysis [10][11][12] and the empirical Hansen-Verlet criterion of freezing [13,14]. The result has been shown to be consistent with one another, both qualitatively and quantitatively, in predicting the existence of terminal 3 polydispersity, beyond which freezing is not possible [9].…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, we can also see from Figure that for δ = 7% and 12%, the system is unable to form crystalline structure and instead forms frozen structure. This is consistent with previous studies on polydispersity, which found that if δ of the system exceeds the terminal polydispersity, then it is unable to crystallize and instead forms glass …”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with previous studies on polydispersity, which found that if δ of the system exceeds the terminal polydispersity, then it is unable to crystallize and instead forms glass. 50 Since our aim is to investigate various properties of the ionic system in liquid phase, we relax the samples at temperature 5% above their respective T h * so that the systems are indeed in the liquid state and at same distance from the respective T h *. This choice of temperatures allows us a better comparison of the systems in their liquid state as fixing the same temperature for all is not ideal due the varying hysteresis loop area as well as thermodynamic melting temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Another class of systems, which demonstrate glass transition, is systems with size polydispersity of particles (see, for instance, Refs [33][34][35]). It was shown in numerous articles that polydisperse hard spheres [33] or Lennard-Jones (LJ) particles [34,35] could demonstrate glass transition if the degree of polydispersity was sufficiently large. At the same time, a polydisperse LJ system looks very different from core-softened systems and one can expect that it should vitrify via some other mechanisms.…”
Section: Introductionmentioning
confidence: 99%